RETIREMENT TRANSITIONS AMONG EMERITI AND THEIR PARTNERS: IMPLICATIONS FOR PROGRAM DEVELOPMENT. (16th November 2018) - Lundell-Creagh, R; Cowan, C; Cowan, P; Sweeney, C; Zedeck, S
Abstract: The transition to retirement marks a monumental occasion in the lives of couples. Past research has focused on easing the stresses associated with this life event. Some suggestions include: Making concrete plans about activities that can be done together, and setting aside time to continue in individual pursuits; Synchronizing the timing of retirement; Communicating concerns and fears to foster greater support However, few studies to date have focused on identifying and assigning valence to the cause of these stressors and determining the extent to which partner discussion can facilitate a resolution. Thus, three important questions remain: What exactly are individuals thinking about as they transition to retirement and to what degree are each of these issues considered? Which issues were discussed and resolved by couples during this transition? Which of these issues remain problematic despite discussion? The purpose of this survey was to answer these questions in an effort to inform future workshops offered by the UC Berkeley Retirement Center in order to best cater to the needs of present and future emeriti.